2012
DOI: 10.1128/aem.06195-11
|View full text |Cite
|
Sign up to set email alerts
|

Heme-Biosynthetic Porphobilinogen Deaminase Protects Aspergillus nidulans from Nitrosative Stress

Abstract: Microorganisms have developed mechanisms to combat reactive nitrogen species (RNS); however, only a few of the fungal genes involved have been characterized. Here we screened RNS-resistant Aspergillus nidulans strains from fungal transformants obtained by introducing a genomic DNA library constructed in a multicopy vector. We found that the AN0121.3 gene (hemC) encodes a protein similar to the heme biosynthesis enzyme porphobilinogen deaminase (PBG-D) and facilitates RNS-tolerant fungal growth. The overproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 44 publications
(58 reference statements)
0
19
0
1
Order By: Relevance
“…Identification of a novel nitrosative stress tolerance gene RIB1. In order to isolate genes involved in nitrosative stress tolerance, the screening was performed in acidified medium (pH 5.5) containing NaNO 2 , as previous studies reported 26,27 . It was previously shown that nitrite induces S-nitrosylation of proteins under acidic condition 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Identification of a novel nitrosative stress tolerance gene RIB1. In order to isolate genes involved in nitrosative stress tolerance, the screening was performed in acidified medium (pH 5.5) containing NaNO 2 , as previous studies reported 26,27 . It was previously shown that nitrite induces S-nitrosylation of proteins under acidic condition 28 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the flavohemoglobins, other proteins have also been found to be involved in the detoxification of NO. For example, the porphobilinogen deaminase hemC acts by promoting the activity of the flavohemoglobins through an unknown mechanism, while the NO-inducible nitrosothionein ntpA scavenges NO through S-nitrosylation in A. nidulans (Zhou et al 2012 , 2013 ). A S-nitrosoglutathione (GSNO) reductase converts GSNO into ammonia and oxidized glutathione (GSSG) in Cryptococcus neoformans and Magnaporthe oryzae (de Jesus-Berrios et al 2003 ; Zhang et al 2015b ).…”
Section: No Homeostasis In Fungimentioning
confidence: 99%
“…NOD activity has been described in the yeast Sa. cerevisiae (Liu et al ., ), Candida albicans (Ullmann et al ., ), Cryptococcus neoformans (de Jesus‐Berrios et al ., ), A. oryzae (Zhou et al ., ), A. nidulans (Zhou et al ., ) and B. cinerea (Turrion‐Gomez et al ., ). Flavohaemoglobins exhibit a dioxygenase activity and contain three domains: a globin domain, a FAD‐binding domain and a NAD(P)‐binding domain.…”
Section: Nitrosative Stress Response In Fungimentioning
confidence: 99%